Integrating local hybrid knowledge and state support for climate change adaptation in the Asian Highlands - Xu, Jianchu; Grumbine, R. Edward (Springer, 2014)
New hybrid forms of climate change adaptation combining local and nonlocal/scientific knowledge are emerging across the Asian Highlands region. Yet, while local adaptive capacity can be based on place-based knowledge that governments often lack, communities still need assistance from states to better adjust to climate change and socioeconomic impacts. Using a regional literature review, we evaluate the role of evolving hybrid forms of adaptive knowledge for coping with environmental and social change. The literature is clear that appreciating local knowledge is not enough; enfranchising people with representative decision-making and resource rights and responsibilities is also required so that people can employ that knowledge toward climate adaptation. Into the future, Asian Highland climate change actions must include more targeted state support for locally evolving hybrid knowledge, behaviors and institutions.